EVALUATING THE EFFECTIVENESS OF “STATPRO” IN ENHANCING SELF-REGULATED LEARNING AND MATH PERFORMANCE IN RURAL SECONDARY EDUCATION - Pramesti, Getut; Widodo, Sri; Utami, Amalia Putri; Nisa, Anita Khoiru; Ulya, Izzatil; Winarsih, Kandhi Tri; Nur Rakhma, Alifia Wahyu (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study examines the effectiveness of the STATPRO game-based learning on mathematics achievement and investigates the factors that influence the formation of self-regulated learning (SRL) among senior high school students in rural areas. Recognizing SRL as a critical factor influencing academic success, creativity, and lifelong learning, this research examines the roles of gender, class, and parental education level in shaping SRL. Employing a quantitative pre-post design using the Wilcoxon-Signed and Friedman test for mathematics achievement and three-way multivariate analysis of variance (MANOVA) for SRL evaluation. Data were collected from cluster-randomized samples across classes 8A to 8C using standardized mathematics tests and the Academic Self-Regulated Learning Questionnaire (ASLQ). Results indicate that class (p = 0.016) and gender (p = 0.001) significantly affect mathematics achievement, while parental education level has no direct impact (p = 0.623). However, SRL development is significantly influenced by the interaction of class, gender, and parental education (p=0.004). These findings highlight the necessity of integrated support from both schools and families to cultivate the students’ self-regulated learning, thereby enhancing students’ cognitive and academic outcomes, especially within resource-limited rural contexts.